KESENJANGAN KUALITAS LAYANAN PENDIDIKAN DI INDONESIA PADA MASA DARURAT COVID-19: TELAAH DEMOGRAFI ATAS IMPLEMENTASI KEBIJAKAN BELAJAR DARI RUMAH - Indah Pratiwi; Bakti Utama (Jurnal Kependudukan Indonesia, 2020)
One of the effects of the COVID-19 pandemic on the education sector in Indonesia is the closure of schools. To ensure education services continue, the government issued a policy of learning home (Belajar dari Rumah/BDR) through online/distance learning. This paper aims to describe the implementation of the BDR for learning quality. To that aim, we have conducted telephone interviews with school principals and teachers from frontier, outermost and remote regions (3T) and non-3T regions. By looking at demographics perspective, implementation of BDR has six variations are a) learning by interactive virtual classroom b) learning assignment by social media c) learning in teacher's or student's home d) learning by using TV/radio e) learning by ‘mouth-to-mouth’ messages and f) learning stopped. The variations generate different quality of learning and will produce an increasing education inequality in Indonesia.